Journalism and Islam (Reflection on the Role of Journalists in the issue of Religious Moderation) - Astinana Yuliarti (State Islamic Institute of Bone, Indonesia, 2020)
AbstractIslam is the majority religion in the country of Indonesia, with the existence of multicultural culture then Islam metamorphosed into a religion that was infiltrated by the views of several groups. The purpose of this study is to analyze how the role of journalists in reporting the issue of religious moderation. The approach used in this research is Robert Entman's framing analysis model with qualitative analysis research type. The data in this study are news stories related to religious moderation in Republika Online Media. The results of the research show that Republika Online media as information media has reported informative and balanced, but it has not been maximized in carrying out the function of media as a Watchdog in the community, as well as the lack of carefulness of Republika journalists in conducting in-depth tracing of informant statements to prevent the habit of information being loaded in the media. Keywords: Framing; Religion Moderation; Online Media.